Intellectual property protection for agricultural biotechnological inventions: a case of Malaysia - Ismail, Suzi Fadhilah (2011)
This research focuses on the current legal protection for agricultural biotechnological inventions in Europe and the U.S. It has been a subject of debate whether plants and agricultural biotechnological inventions which includes plants, transgenic plants and plant varieties, can be the subject of patent protection, in addition to or as an alternative to the protection afforded by plant variety rights. Biotechnological patents have been criticized for granting an excessive scope of protection to proprietors, whereas plant variety rights have been slighted for not providing enough protection. Hence, this research is built on a few main themes, namely; the discussion of IP protection for agricultural biotechnological inventions as currently in practice in Europe and the U.S., as well as the deliberation on the current system as practised in Malaysia. The research also discusses the issue of the interface between the patent regime and plant variety rights over agricultural biotechnological inventions as there are possible overlaps between the two systems, notwithstanding the exclusivity of protection of plant varieties under the PVR system.